2020
DOI: 10.21203/rs.3.rs-40902/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Implementation of the SWITCH® School Wellness Intervention and Capacity-Building Process through Multiple Methods

Abstract: Background: School wellness programming is important for promoting healthy lifestyles and academic achievement in youth; however, research is needed on methods that can help schools implement and sustain such programs on their own. The purpose of this study was to investigate factors within and outside the school environment that influenced school capacity for implementation and potential sustainability of wellness programming. Methods: As part of the School Wellness Integration Targeting Child Health (SWITCH®… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several tools only measured delity and/or adoption as the implementation outcomes, which draws concern for addressing constructs such as feasibility and sustainability, among others. Only 8 measures addressed feasibility, with 7 of those within unique tools; this is somewhat contradictory to the extant literature on school-based programming, as many studies have reported low feasibility for implementing policies and health promoting interventions (26,(59)(60)(61). Further, through qualitative and mixed-methods research it has transpired that, despite providing nancial and logistical support to schools, districts, and states/provinces, most policies are di cult to sustain in absence of such support (61)(62)(63).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several tools only measured delity and/or adoption as the implementation outcomes, which draws concern for addressing constructs such as feasibility and sustainability, among others. Only 8 measures addressed feasibility, with 7 of those within unique tools; this is somewhat contradictory to the extant literature on school-based programming, as many studies have reported low feasibility for implementing policies and health promoting interventions (26,(59)(60)(61). Further, through qualitative and mixed-methods research it has transpired that, despite providing nancial and logistical support to schools, districts, and states/provinces, most policies are di cult to sustain in absence of such support (61)(62)(63).…”
Section: Discussionmentioning
confidence: 98%
“…Within this broader construct, non-training resources was the most common determinant assessed; provision of nancial resources and personnel support have been cited as supportive factors for policy and innovation implementation in school research (9,74,75). Following this, leadership for implementation was very prevalent in the measures, which again re ects extant knowledge that new innovations require a leader to succeed (61,76,77). Finally, the prevalence of items measuring communication of policy demonstrated the importance of engaging stakeholders in policy implementation through enhancing awareness of such initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Tangney et al shows that self-control is closely related to students' performance and academic success [16]. Vazou et al further discuss that self-control and other cognitive functions can be nurtured through intervention [17]. For example, Meichenbaum and Goodman proposed training children to talk to themselves improves ability to control their emotions [18].…”
Section: Related Literaturementioning
confidence: 99%